Kreatif dan Inovatif Melalui Pelatihan Membuat Buket Snack Sebagai Alternatif Buah Tangan Bagi Santri - Hukama, La Diadhan; Simon, Zainal Zawir; Juniarti, Juniarti; Zain, Efendi (Journal of Dedicators Community, 2022)
The tradition of giving gifts is something that is common and common to individuals from various circles of society. Snack bouquets can be used as an alternative gift that can be given to others, such as when there is a grade increase or graduation celebration. Snack bouquet is a series of snacks (snacks) that are arranged, arranged, arranged like a bouquet of flowers. This activity aims to increase the capacity and skills of students through training in making snack bouquets for students at the Daarul Uluum I Islamic Boarding School in Bogor City. One of the alternative steps to increase the creativity and innovation of students, in this community service activity, uses the ABCD (Asset Based Community Development) approach. Meanwhile, in the practice of making a snack bouquet, the Peer Assisted Learning model is used. As a result of this community service activity, participants were able to make a snack bouquet. In addition, the participants were very enthusiastic about participating in the training from start to finish.